A comprehensive analysis of Indonesia’s education quality development across infrastructure, curriculum, teacher competence, technology, and character education - Kristiyuana Kristiyuana; Eko Handoyo (Institute of Computer Science (IOCS), 2026)
Education is the main foundation in building quality and competitive human resources (HR) in the global era. The quality of education is an important indicator in determining a nation's ability to face technological developments, global competition, and the demands of 21st century competencies. This study aims to describe the policy of developing the quality of education in Indonesia through several main aspects, namely strengthening infrastructure, revitalizing the curriculum, improving the quality of teachers, utilizing educational technology, character education, and learning from international practices. The study was carried out through a literature study of policy documents, government reports, and previous research. The results of the study show that education policies in Indonesia have moved towards a more adaptive direction, including the implementation of the Independent Curriculum, the Teacher Driving program, school digitalization, and strengthening the Pancasila Student Profile. However, challenges such as infrastructure inequality, teacher competency gaps, low digital literacy, and uneven implementation of P5 are still obstacles. This article contributes theoretically and practically to education policy studies in Indonesia by providing an integrative analytical framework for evaluating policy directions in education quality improvement and offering strategic insights to support evidence-based and sustainable policy formulation. It is necessary to strengthen governance, equitable distribution of facilities, increase teacher capacity, and cross-sector collaboration to support the sustainable development of education quality.